PERLINDUNGAN HUKUM TERHADAP INVESTOR DALAM PERJANJIAN PINJAM MEMINJAM SECARA ONLINE (PEER TO PEER LENDING) DI PLATFORM TANIFUND - Dayanty, Asty Thania; Pasaribu, Chrisnoven; Syahfitri Sigalingging, Yeni; Alvines, Alvines; Hasudungan Sianturi, Ronald (Universitas Ekasakti, 2021)
Through P2P Lending, we can invest. The purpose of this research is to analyze the parties responsible for the Loan Facility Distribution Agreement on the TaniFund Platform, along with legal protection for investors. In this research, we used juridical-normative and descriptive research..Theresults ofthis studyare basedon the agreementon theTaniFundplatform, the lender iscategorized as alender where the organizer is not responsible for the risk of borrowing and interest losses due to default of the loan recipient. Legal protection for investors is stated in article14 LawNumber 25of2007 concerning Investment. Based on agreements on the TaniFund platform, lenders can conduct deliberations or sue to the general court inthe eventof adispute with the organizer. Researchers hope that the government can be more optimal in supervising P2PLending platforms in Indonesia, so that organizers do not arbitrarily include the transfer of responsibility in making standard agreements that can harm investors.